Linking dietary fatty acids to mesocorticolimbic networks controlling appetite. (June 2022) - Hryhorczuk, Cécile; Nakajima, Shingo; Fulton, Stephanie
Abstract: Fatty acids derived from diet play a considerable role in the regulation of energy metabolism. Orosensory, gut-brain, and humoral pathways participate in detecting and channeling fatty acid signals to diverse circuits; however, fatty acids can also have direct central actions by crossing the blood–brain barrier. Mounting findings are uncovering the molecular machinery responsible for the modulation of excitability and signaling of neural cells in response to fatty acids. This review describes the properties of fatty acids, routes through which they affect brain function and their impact on neurobehavioral mechanisms related to appetite with a focus on mesocorticolimbic networks controlling motivation.